The Role of Clomiphene Citrate in Gonadotropin Stimulation Protocols in Poor Responders: A Mini-Review of Recent Clinical Evidence - Maria Papadopoulou; Miltiadis Badagionis; Fotios Vlahos; Nikolaos Vlahos; Alexandros Lazaridis; George Mastorakos; Olga Triantafyllidou (Reproductive Medicine, 2026)
Diminished ovarian reserve (DOR) and poor ovarian response (POR) remain among the most challenging conditions in assisted reproductive technology, and no optimal stimulation strategy has been established. Clomiphene citrate (CC), a selective estrogen receptor modulator that augments endogenous gonadotropin secretion and modulates the intraovarian androgenic milieu, has been proposed as an adjuvant to reduce exogenous gonadotropin requirements. This mini-review summarizes clinical evidence published between January 2015 and March 2025 on the co-administration of CC with gonadotropins in women with DOR or POR undergoing IVF/ICSI. Eleven primary studies (four randomized controlled trials, six observational cohort studies and one before–after study) were identified through a structured, PRISMA-informed literature search. Across mild, standard, and high-dose regimens, CC co-administration consistently reduced total gonadotropin consumption and stimulation duration, whereas oocyte yield, clinical pregnancy, and live-birth rates were largely comparable to conventional protocols. Cost analyses suggest a meaningful reduction in the expenditure per treatment cycle, although the cost per delivery is driven predominantly by the low absolute success rates in this population. Careful monitoring of endometrial thickness is warranted given the anti-estrogenic effect of CC, and a freeze-all strategy may be preferable when endometrial development is suboptimal. In the wider context of adjuvant therapy for POR, CC occupies a position comparable to that of letrozole: it reduces treatment burden without demonstrable improvement in live birth. Larger, adequately powered multicentre randomized trials with live birth as the primary endpoint are needed to define the role of CC in this population.